A New Pixel Circuit to Compensate Panel Non‐uniformity and OLED Degradation on Large IGZO AMOLED Panel. Issue 1 (June 2014) - Lin, Chun‐Chieh; Lee, Kuei‐Yu; Chen, Chih‐Cheng; Lin, Hong‐Shen; Chang, Lee‐Hsun; Lin, Yu‐Hsin
Abstract A new 4T2C pixel circuit is proposed in this study to compensate TFT process variations, Vth, mobility, power line IR‐drop, and OLED degradation in IGZO‐TFT process. Compensation performances show only from ±0.8% to ±1.74% panel non‐uniformity in average.